Situating Exclusion of Evidence Analysis in its Socio-Legal Place: A Tale of Judicial Populism. - Jochelson, Richard; Kramar, Kirsten (Crime, Law & Social Change, 2014)
In the 2009 case of R. v. Grant, the Supreme Court of Canada reformulated the exclusion of evidence framework in the context of Charter breaches. The case was something of a revolution for those who study evidence law and the Charter. Thus far, the case has been the subject of much debate and even empirical study. Few academic papers have explored the philosophical predilections of the Court in the decision. In this paper, the authors briefly review the history of the exclusion of evidence test, explain the new framework and discuss the academic and legal responses to the case. The authors place the reasoning of the Court in a broader socio-legal context arguing that the test articulated by the Court is informed by a type of populism that combined with recent Charter cases in the police powers context allows for flexible potentials, ones that could, on occasion, encroach on due process protections. The authors call for scholars and activists to keep a close eye on the emerging jurisprudence in this critical area of Charter adjudication.